Maternal Risk Factors for Small-for-Gestational-Age Newborns in Mexico: Analysis of a Nationwide Representative Cohort - L, Suárez-Idueta; H, Bedford; EO, Ohuma; M, Cortina-Borja (Frontiers in Public Health, 2021)
Background Small for gestational age (SGA) is a key contributor to premature deaths and long-term complications in life. Improved characterization of maternal risk factors associated with this adverse outcome is needed to inform the development of interventions, track progress, and reduce the disease burden. This study aims to identify socioeconomic, demographic, and clinical factors associated with SGA in Mexico. Methods We analyzed administrative data from 1,841,477 singletons collected by the National Information Subsystem of Livebirths during 2017. Small-for-gestational-age was defined as being <10th centiles according to the INTERGROWTH-21st standards. The comparison group was defined as being in ≥10th centiles. We fitted logistic regression models to determine odds ratios for the maternal factors associated with SGA. Results Of the 1,841,477 singletons, 51% were male, 6.7% were SGA, 6.1% were term-SGA and 0.5% were preterm-SGA. Maternal education presented a protective gradient of being SGA among mothers who achieved 1 to 6 years of education (adjusted Odds Ratio (aOR) 0.95 95% Confidence Interval, CI, 0.91, 0.99), 7 to 9 years (aOR 0.86 95%CI 0.83, 0.89), 10 to 12 years (aOR 0.75 95%CI 0.72, 0.79) and >12 years (aOR 0.63 95%CI 0.60, 0.66) compared with those without education. SGA was particularly likely to occur among primiparous (aOR 1.42 95%CI 1.39, 1.43), mothers living in very high deprivation localities (aOR 1.39 95%CI 1.36, 1.43), young (aOR 1.04 95%CI 1.02, 1.06), advanced age (aOR 1.14 95%CI 1.09, 1.19), and mothers living in areas above 2,000m (aOR 1.69 95%CI 1.65, 1.73). Antenatal care was associated with a reduced risk of SGA by 30% (aOR 0.70, 95%CI, 0.67, 0.73), 23% (OR 0.77, 95%CI, 0.74, 0.80) and 21% (0.79, 95%CI, 0.75, 0.83), compared with those mothers who never received antenatal care, when women visited the clinic at the first, second and third trimester, respectively. Conclusion Almost 7% of live births were found to be SGA. Parity, maternal age, education, place of residence, and social deprivation were significantly associated with this outcome. Antenatal care was protective. These findings imply that interventions focusing on early contact with health care facilities, reproductive health counselling, and maternal education should reduce SGA in Mexico.